Hubungan Religiusitas dengan Self-Awareness Siswa Sma Bodhicitta Buddhis School Medan - Janice Jeconiah; Venny Oktavia; Wasuki; Yulinda Septiani Manurung (Journal of Research in Business, Economics, and Education, 2021)
This study aims to determine the relationship between religiosity and self- awareness of students in Bodhicitta Buddhis Senior High School Medan. The hypothesis in this study is that there is positive relationship between religiosity and self-awareness of students in SMA Bodhicitta Buddhist School Medan. The research subjects used in this study were 137 students in class XII using the proportionate stratified random sampling method. This research uses quantitative methods, the research data collected using the scale of religiosity with 44 items and self-awareness scale with 31 items. The assumption test used consists of a normality test and a linearity test. Data were analyzed using Pearson Product Moment correlation test with the help of SPSS 20 for Windows. The results of data analysis showed a positive relationship between religiosity and self-awareness in SMA Bodhicitta Buddhist School Medan students with a Pearson Product Moment correlation coefficient of r = 0.355 with sig. 0,000 (p <0.005). The results of this study indicate that the contributions made by the variable of religiosity on self-awareness was 12,6 percent, while the remaining 87,4 percent was influenced by other factors that were not examined. From these results, it is concluded that the hypothesis, which stated that there is a positive relationship between religiosity and self-awareness, is acceptable.